Tolerable Deviance and How it Applies to Cyberbullying. Issue 1 (2nd January 2019) - Harper, Molly-Gloria
ABSTRACT: As a result of the modern youth culture's reliance on technology and instant communications, mainly through social media platforms, bullying has transitioned to the online domain where cyberbullying has emerged. Among youth, cyberbullying can be viewed as a type of tolerable deviancy where youth often do not question the deviant nature of their online behaviors. This research explores the creation of the scale of deviancy as developed through a qualitative popular film analysis where low-, moderate-, and high-level deviancy characterize various cyberbullying behaviors and captures the essence of the escalation of harm faced by cyber victim(s).